Introduction: Regulation and Domestic Service in Colonial Histories. (April 2022) - Haskins, Victoria; Sen, Samita
Abstract: This essay introduces the Special Theme on regulation and domestic service in colonial societies. It provides a brief overview of the key themes of domestic service and regulation in the history of colonial states, and reflects upon the ways in which the colonial past is deployed in contemporary calls for the regulation of domestic work by the state, to secure the rights and protections of present-day workers as modern, free subjects. We note that, while much more work needs to done on this subject, current scholarship suggests that the status of the domestic worker and the extent of regulation in colonial contexts was historically unclear and often ambivalent. The three articles that constitute the Special Theme are then discussed in turn, to highlight the important insights, both empirical and theoretical, they offer to our deeper understanding of this complex history.